Text Data Security Application Using a Mobile-Based Base64 Algorithm - Rifki, Mhd Ikhsan; Muhammad Ezar Raditya; Abdul Halim Hasugian (Bahasa Indonesia, 2023)
During the process of sending data or information on a communications network, various types of data and important information related to personal data and identity are often transacted on the network. This can be exploited by irresponsible parties to gain personal gain by duplicating personal data or information. So, protection is needed for data sent via communication networks. According to Law No. 27 of 2022, personal data protection includes all efforts to protect personal data and guarantee the constitutional rights of personal data subjects. Based on this, the research objective is to provide users with options to provide additional security for text data in the form of personal data. The base64 application provides data security by changing plaintext into ciphertext, which has an information structure that is very different from the original form of information. The text data security application using the base64 algorithm was designed using the Unified Modeling Language (UML) system development method. Regarding application development, the framework used is modular. So, with this application, text data has additional data security options to avoid behavior that could be detrimental.